Walking on the pages of the Word of God : self, land, and text among Evangelical volunteers in Jerusalem - Engberg, Aron, (Currents of Encounter;, 2019)
In Walking on the Pages of the Word of God Aron Engberg explores the religious language and identities of evangelical volunteer workers in contemporary Jerusalem. The volunteers are connected to Christian organizations which consider their work a natural consequence of the biblical promises to Israel and their responsibility to "bless the Jewish people". Relying on ethnographic data of the discursive practices of the volunteers, the book explores a central puzzle of Zionist Christianity: the narrative production of Israel's religious significance and its relationship to broader Christian language traditions. By focusing on the volunteers' stories about themselves, the land and the Bible, Aron Engberg offers a convincing account about how the State of Israel is finding its way into evangelical identities.